1969
DOI: 10.1177/001872086901100606
|View full text |Cite
|
Sign up to set email alerts
|

Models, Measures, and Judgments in System Design

Abstract: This paper assumes increasing use of analytical models in system design. Some characteristics of such models and requirements for human performance data compatible with them are discussed. Methods of obtaining human performance data for use in design models are considered. The use of expert judges to generate performance measures is reviewed. Two new studies are reported in support of the proposition that expert judgments may offer a practical method of obtaining performance measure with potentially wide appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1970
1970
1986
1986

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A previous paper (Knowles, Burger, Mitchell, Hanifan, and Wulfeck, 1969) addressed to the increasing use of analytical models in system design discussed some characteristics of such models and their requirements for human performance data. Methods of obtaining human performance data for use in analytical models were considered, and the use of expert judges to generate performance measures was reviewed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous paper (Knowles, Burger, Mitchell, Hanifan, and Wulfeck, 1969) addressed to the increasing use of analytical models in system design discussed some characteristics of such models and their requirements for human performance data. Methods of obtaining human performance data for use in analytical models were considered, and the use of expert judges to generate performance measures was reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Those findings suggested that the statistical reliability of performance reliability estimates could be improved by developing techniques to identify and capitalize on the systematic effects among tasks and judges (Knowles, et al, 1969).…”
Section: Introductionmentioning
confidence: 99%